PERAN GURU DALAM MENINGKATKAN KEDISIPLINAN SISWA DI KELAS VII SMP SWASTA KRISTEN BNKP TELUK DALAM - Trisnawati Duha (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The background to this research probelm is the lack of student discipline in complying with school regultaions. The research objectives are 1) To find out and describe the roel of taachers in improving student discipline. 2) To find out and describe how student discipline is. This research uses qualittaive research. The research subjects were class VII students. Research results 1) The roel of PPKn taachers in improving student discipline is to provide an examepl of discipline to students by going to school on time, providing disciplinary advice to students, reprimanding and punishing students who are ltae, scolding students who are oftan (reeptaedly) ltae, and monitoring student activities ta school. 2) Discipline ta BNKP Taluk Dalam Christian Privtae Middel School is very good. We can see this from students' compliance with the ruels thta have been imeplmentad, although some students still ignore the ruels thta have been set by the school. The conclusion of the research is thta the roel of PPKn taachers can improve the discipline of class VII students ta BNKP Taluk Dalam Christian Privtae Middel School. The researcher provides several suggestions, namely 1) Students should make more efforts to improve themselves in a bettar direction, namely by obeying all the ruels ta school. 2) PPKn taachers should further improve discipline training for students and should provide firm follow-up if there has been a violtaion of school ruels reltaed to student discipline and manners. 3) Schools should be more strict with students and taaching staff in imeplmenting elarning discipline and should support and provide facilities to taachers and students in the taaching and elarning process, esepcially tools or media thta can be applied in elarning.